(untitled) (Academia Journal of Medicine, 2025)
Child nutrition plays a crucial role in physical growth, cognitive development, and overall health outcomes. Proper nutrition during early life stages is critical to achieving optimal growth, preventing diseases, and ensuring the full realization of a child’s genetic potential. This review summarizes the current evidence on the role of child nutrition in growth and development, focusing on the importance of macronutrients, micronutrients, and dietary diversity